THE LIFE STRUGGLEOF FEMALE CHARACTERS IN THE NOVELSOF ABIDAH EL KHALIEQY - Yenny Puspita; Zainal Rafli (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This study aimed to obtain a deep picture and understanding of the life struggle of female characters in the novel written by Abidah El Khalieqy. The research design used was descriptive qualitative with feminism approach. The data in this research were the study results of the novel documents of Perempuan Berkalung Sorban and Geni Jora by Abidah El Khalieqy in the form of words, sentences in the form of utterances, description of figures and inter-character dialogues indicating the  existence of feminism that happened to the analyzed figures of the novel. The procedure in analyzing research data was content analysis. The data validity analysis utilized triangulation technique. Based on the results of research and discussion, it was found that the struggles to fight the injustice among them were the struggle against: 1) marginalization of women; 2) subordination to women; 3) stereotypes about women; and 4) violence against women, including the struggle against physical, sexual and psychological violence; and 5) the struggle against women'sworkload.